Public reading interest through utilization of iPusnas National Library of the Republic of Indonesia - Aini, Hanna Nabiila Qurota; Prijana, Prijana; Rohman, Asep Saeful (Universitas Padjadjaran, 2025)
Reading activities can reach an optimal level if individuals have a high interest in reading. iPusnas is one of the media that can increase public reading interest. This study aimed to determine the correlation between public reading interest and the iPusnas National Library of the Republic of Indonesia by analyzing academic needs, professional needs, improved welfare, and increased income. This study used a quantitative approach with a survey method on the community of iPusnas users. The sampling technique used was quota sampling with a sample size (n) of 444. The data collection technique used was primary data obtained through online questionnaires filled out by respondents, and literature studies to strengthen the research results. The results of the study indicated that the reading interest of iPusnas users had a relationship pattern with the fulfillment of various needs and user interests through ease of access and the availability of up-to-date collections. In terms of academic needs, professional needs, and improving welfare, the correlation coefficient was moderate. Besides, in the aspect of increasing income, the correlation coefficient figure was below moderate. This showed that the iPusnas application was more effective in supporting educational and professional needs than the income aspect. This study concludes that the iPusnas application is effective in fostering reading interest through the provision of access to relevant and quality information according to the needs and interests of iPusnas users.